Medical Play Intervention as an Atraumatic Care Approach for Hospitalized Preschool Children: A Systematic Literature Review - Titik Anggraeni; Sarwoko; Herbasuki; Sri Sayekti Heni Sunaryanti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2026)
Hospitalization in preschool children can cause anxiety, fear, psychological stress, and uncooperative behavior during hospital treatment. Medical play is one of the atraumatic care approaches used to reduce the negative impacts of hospitalization on children. This study aimed to analyze the effectiveness of medical play interventions as an atraumatic care approach for hospitalized preschool children. The research method used was a Systematic Literature Review following the PRISMA guidelines. Articles were searched through the PubMed, Scopus, and ScienceDirect databases using keywords related to medical play, atraumatic care, preschool children, and hospitalization. The articles included were primary studies published between 2020–2025 that met the inclusion and exclusion criteria. A total of 9 primary articles were analyzed in this study. The synthesis results showed that medical play interventions were effective in reducing anxiety, fear, hospitalization stress, and psychological trauma in preschool children. In addition, medical play also improved children’s cooperative behavior during medical and nursing procedures. The forms of intervention included therapeutic play, storytelling, pretend play, and the use of toy medical equipment. The study concludes that medical play is an effective non-pharmacological intervention in the implementation of atraumatic care for hospitalized children. These findings can serve as a basis for the development of evidence-based nursing in pediatric nursing services and support the optimal implementation of atraumatic care in pediatric wards.